The correlation of serum level and gene polymorphisms of interleukin-33 in atopic dermatitis Iraqi patients - Hiba Dhia Jafer; Aseel S. Mahmood (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Atopic dermatitis (AD), also known as atopic eczema, is a chronic relapsing inflammatory skin condition. Interleukins-33 (IL-33) are inflammatory cytokines that highly expressed in the keratinocytes of AD-suffering patients. This study aimed to investigate the correlation of the IL-33 serum levels and single nucleotide polymorphisms (SNP) of its gene in the rs10975519. This study includes 100 patients with atopic dermatitis (AD) and 80 healthy controls. The result indicate there was no significant difference when compared between the body mass index (BMI) of patient and control groups. In addition, there were non-significant increase in the concentration of eosinophil in AD patients, in comparison with controls (p<0.553). While result of the total Immunoglobulin E (tIgE) was showed a high significant increase in t-IgE in patients with AD compared with controls (p<0.001). The findings showed that serum level of IL-33 was highly increased in patients of AD in compared with controls with (p<0.001). Also, no significant variations of IL-33 serum levels (p-value = 0.01), with age, gender, BMI, IgE, eosinophilia and duration of disease. Only age showed a significant correlation with IL-33 among patients and controls (p<0.001). SNPs rs10975519 of IL-33 gene was also investigated, and the result indicates that the patients whose carry elevated frequencies of both codominant CT, TT, dominant (CT+TT) or allele T of rs10975519 SNP are more likely infected with AD with odd ratios (2.4, 3.7, 6.2 and 1.8, respectively) among patient and control groups. No significant differences were observed in serum levels of IL-33 with its related-SNPs (rs10975519).